2019
DOI: 10.1039/c8ta12443d
|View full text |Cite
|
Sign up to set email alerts
|

Outstanding cycle stability and rate capabilities of the all-solid-state Li–S battery with a Li7P3S11 glass-ceramic electrolyte and a core–shell S@BP2000 nanocomposite

Abstract: A Li7P3S11 glass-ceramic solid electrolyte and a core–shell S@BP2000 nanocomposite are used to fabricate all-solidstate Li–S batteries, which exhibit outstanding cycle stability and rate capabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 47 publications
0
47
0
Order By: Relevance
“…It was confirmed that a homogeneous distribution of active materials, SSEs, and conductive carbon exhibited a promising approach to alleviate the challenges in the way of practical application. Han [ 144 ] et al. developed a core–shell structured S@BP2000 nanocomposite cathode (Figure 10b).…”
Section: Cathode Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…It was confirmed that a homogeneous distribution of active materials, SSEs, and conductive carbon exhibited a promising approach to alleviate the challenges in the way of practical application. Han [ 144 ] et al. developed a core–shell structured S@BP2000 nanocomposite cathode (Figure 10b).…”
Section: Cathode Preparationmentioning
confidence: 99%
“…Reproduced with permission. [ 144 ] Copyright 2019, The Royal Society of Chemistry. c) Schematic illustration of (top) CNT@S with uniform electronic pathway and (bottom) CNT/S with uneven electronic pathway.…”
Section: Cathode Preparationmentioning
confidence: 99%
“…[27][28][29] Yu et al used ball milling and heat treatment to get composite particles can deliver an initial discharge capacity of 1523 mAh g À 1 ( 91% ) at 0.1 C. [30] Yamada et al used Li 3 PS 4 and high energy ball milling to get amorphous composite particles can exhibit discharge capacity of 1600 mAh g À 1 ( 95% ) at 0.05 C. [31] Han et al used ball milling and heat treatment to get 5 nm core-shell S@BP2000 composite can achieve large interface area between sulfur nanoparticles and porous carbon, and achieved the discharge capacity of 1391.3 mAh g À 1 ( 83% ) at 0.2 C and 678.6 mAh g À 1 at 4 C at RT with high sulfur utilization under high discharge-charge rate. [32] By reason of the high speed running and longtime milling, a lot of energy is consumed, which makes the large-scale production and its practical application more difficult. In addition, the repeatability of the mechanical milling is low and it is difficult to obtain a uniform composite electrode.…”
Section: Introductionmentioning
confidence: 99%
“…With a rGO@S–Li 10 GeP 2 S 12 –acetylene black composite, a capacity of 903 mAh g −1 was obtained at 1C at 60 °C, which was maintained at 830 mAh g −1 after 750 cycles [487]. Most of all, Li 7 P 3 S 11 glass-ceramic solid electrolyte with a high ionic conductivity and a composite cathode made of sulfur and BP2000 porous carbon (S@BP2000) with a core-shell structure were used to fabricate a novel all-solid-state sulfur battery [488]. Owing to the ionic conductivity of Li 7 P 3 S 11 (2 × 10 −3 S cm −1 at room temperature, the cell delivered a capacity of 1391 mAh g −1 at 0.2C and 677 mAh g −1 at 5C, and a capacity retention of nearly 100% after 1200 cycles was obtained, for a mass loading of the cathode of 2 mg cm −2 .…”
Section: Li–s Cellsmentioning
confidence: 99%